Faith communities, youth and development in Mozambique - Chifeche, Victoria; Dreyer, Yolanda (HTS Teologiese Studies / Theological Studies, 2019)
In Mozambique, poverty is pervasive because of factors such as the civil war (1976–1992) and its aftermath, political instability, food scarcity and natural disasters. This article elucidates the situation of post-civil war Mozambique from a socio-political perspective with a specific focus on children and the youth as a particularly vulnerable group. Many children and young people have been displaced and are subject to work exploitation and sexual abuse. Female children also fall victim to the cultural practice of child marriage. The absence of comprehensive social measures for the protection of vulnerable young persons has a detrimental effect on their welfare and future prospects. The aim of the article is to explore the role that faith communities and church institutions can play in this context. From an inclusive congregational perspective, the inclusion of youth in all aspects of faith communities as a strategy for development is discussed. From a human rights and theological perspective, participatory action is required for faith communities and church institutions to contribute to making a life of human dignity possible for children and young people.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; gender / género; institutions / instituições; youth / juventude